Public Response to Social Media Campaigns on the Dangers of Smoking and the Prevention of Chronic Obstructive Pulmonary Disease - Reyza, Muhammad Fakhrul; Nursiswati, Nursiswati (Universitas Padjadjaran, 2025)
Cigarettes have thousands of free chemical compounds that contain harmful toxicity so that they can attack the body system, especially in the respiratory tract. One of the effects of smoking is the onset of Chronic Obstructive Pulmonary Disease (COPD) which contributes to the high number of diseases that cause death in the world. So that health education is needed using social media Instagram with the topic “Stop Smoking as Prevention of Chronic Obstructive Pulmonary Disease”. The service aims to determine the community's response on Instagram social media after watching health education content on the dangers of smoking as a major risk factor for COPD. The data analysis method used is descriptive quantitative and qualitative based on the type and number of responses that have been given by the community in the comments column. The content was presented in the form of videos, animations, and posters that included information on the definition, prevalence, causes, signs and symptoms, risk factors, impacts, treatments, and prevention of COPD. Within six days, there were 634 likes and 106 comments from respondents. In the comments section, 82 respondents (77%) agreed with the message conveyed in the content. A total of 7 respondents (6.7%) admitted that it was still difficult to leave cigarettes after watching the content, and 17 respondents (16%) stated that they were passive smokers. Qualitative results showed three themes including difficulties in quitting smoking, awareness and empathy, and appreciation of the content. This health education program through social media about COPD received positive responses, providing new knowledge about this disease and the importance of quitting smoking to the general public. In addition, it is recommended to conduct continuous health education to reduce the number of active and passive smokers. Keywords: Health education, campaign, smoking, COPD, social media